Bringing Intimacies into the Discussion: On the Relevance of Addressing Intimate Relationships in a Migration Context - Röhm, Mona; Justus Liebig University Giessen (My University, 2020)
Topics such as gender, sexualities, and intimacies, recently experienced processes of instrumentalization and culturalization in European public and political discourses on migration matters. Culturalization is particularly the case when it comes to questions of integration where the cultural Other is contrasted to European values to legitimate political objectives. Romantic love as a marker of living a morally right intimate relationship is in this regard implicitly used to illustrate an incompatibility of Muslim migrants to European ideals of intimacy. Based on conceptual thinking and literature review, this theoretical paper highlights the relevance of addressing intimacies, practices, and intimate ideas within current migration debates in Europe and Austria in particular. It is illustrated that there is a need to link the rising research stream on mobile intimacies to recent Anti-Muslim developments in European discourses. With the concept of belonging, the paper provides a possible approach to understand processes of exclusion and inclusion based on intimate ideas and shows their negotiable character. Further, this paper emphasizes the importance of thinking about Euro-Centric precategorizations and encourages micro-sociological inductive research to grasp the diverse understandings and practices of intimacies.
Keywords: intimacies; gender; migration; integration; othering; belonging; ddc:300